Eduard C. Lindeman and Social Work Philosophy - Konopka, Gisela (Book collections on Project MUSE., 1958)
Eduard C. Lindeman, a leader in the field of social work for many years, was deeply concerned with the professions development of a basic philosophy. As a teacher at the New York School of Social Work for more than 25 years and as a prolific writer and c.